Green office buildings and sustainability: Does green human resource management elicit green behaviors?. (20th December 2021) - Parida, Subhadarsini; Ananthram, Subramaniam; Chan, Christopher; Brown, Kerry
Abstract: Green buildings are synonymous with environmental sustainability; however, it is unclear what role its occupants, specifically employees, play in promoting sustainability in green office buildings. This paper proposes that Green Human Resource Management (HRM), underpinned by Social Identity Theory (SIT), can maximize the potential of green behaviors to improve employees' outcomes (e.g., job satisfaction and work-related flow) in green office buildings by creating positive workplace behaviors (i.e., green behaviors). We collected multisource data from 549 employees and 91 managers working in 17 organizations in green office buildings across Australia. We confirm the double mediation effects of Green HRM, green behaviors and organizational identification on the relationships between organizational readiness, job satisfaction and work-related flow. The paper makes theoretical contributions by advancing the concept of Green HRM and green behaviors within the realm of SIT, thus taking a multidisciplinary stance in the built environment and sustainability literatures.